Paroxysmal Nocturnal Hemoglobinuria: Diagnostic Challenges in Pediatric Patient - Dharshana Krishnaprasadh; Inna Kaminecki; Anna Sechser Perl; Jonathan Teitelbaum (Case Reports in Pediatrics)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare, life-threatening hematologic stem cell disorder characterized by hemoglobinuria, thrombosis, and tendency for bone marrow failure. The rare incidence of PNH in children, its nonspecific clinical presentation, and occasional absence of hemoglobinuria make the diagnosis challenging. We present a case of a 17-year-old boy who was hospitalized with a history of recurrent abdominal pain, fever, and dark-colored urine. Laboratory tests revealed anemia, thrombocytopenia, and elevated inflammatory markers. Urinalysis was positive for protein and red blood cells, too many to be counted. Complement studies were within normal limits. Abdominal computed tomography showed a segment of the small bowel with wall thickening and signs of possible microperforation. Exploratory laparotomy revealed necrosis of the small bowel, and histological evaluation was suggestive of an autoimmune process with small vessel vasculitis. Bone marrow biopsy showed hypocellular marrow with a decreased number of myeloid cells, normal number of megakaryocytes, and signs of erythroid hyperplasia. Flow cytometry detected deficiency of CD59 leading to the diagnosis of PNH. The patient was treated with eculizumab infusions resulting in significant improvement. This case highlights the need for high clinical suspicion for rare entities such as PNH in patients presenting without hemoglobinuria.